Aetiology of hyperthyroidism in Canada and Wales. Issue 3 (September 1983) - Williams, I; Ankrett, V O; Lazarus, J H; Volpe, R
Abstract : A retrospective, comparative review of 100 consecutive new outpatients presenting with hyperthyroidism in Cardiff, South Wales, and in Toronto, Canada, was performed. The aim was to quantify the causes of hyperthyroidism with particular emphasis on the prevalence of viral thyroiditis and "silent" thyroiditis. The proportional morbidity of Graves' disease (approximately 70%) was similar in the two groups. Toxic multinodular goitre and toxic adenoma (Plummers' disease) occurred significantly more frequently in Cardiff (25% v 8%), whereas thyroiditis predominated in Toronto (17% v 1%).